Histone Chaperones as Cardinal Players in Development - Rajam, Sruthy Manuraj; Varghese, Pallavi Chinnu; Dutta, Debasree (Frontiers in Cell and Developmental Biology, 2022)
Dynamicity and flexibility of the chromatin landscape are critical for most of the DNA-dependent processes to occur. This higher-order packaging of the eukaryotic genome into the chromatin is mediated by histones and associated non-histone proteins determine the states of chromatin. Histone chaperones- “the guardian of genome stability and epigenetic information” controls the chromatin accessibility by escorting the nucleosomal and non-nucleosomal histones as well as their variants. This distinct group of molecules is involved in all facets of histone metabolism. The selectivity and specificity of histone chaperones to the histones determine the maintenance of the chromatin in an open or closed state. This review highlights the functional implication of the network of histone chaperones in shaping the chromatin function in the development of an organism. Seminal studies have reported embryonic lethality at different stages of embryogenesis upon perturbation of some of the chaperones, suggesting their essentiality in development. We hereby epitomize facts and functions that emphasize the relevance of histone chaperones in orchestrating different embryonic developmental stages starting from gametogenesis to organogenesis in multicellular organisms.